Developing people's information capabilities fostering information literacy in educational, workplace and community contexts - Hepworth, Mark, 1955-; Walton, Geoff (Emerald, 2013)
Developing people's information capabilities : fostering information literacy in educational, workplace and community contexts is Vol 8 of the well regarded Library and Information Science Series. This book hones in on accessible issues across different work and educational contexts and is of value to both academic and practitioner.
Includes index.
Keywords: Information literacy -- Study and teaching.; elektronické knihy; electronic books